Bank Privatization In Sub-Saharan Africa : The Case of Uganda Commercial Bank - Clarke, George R. G. (The World Bank, 2007)
Previous empirical analyses have found that bank privatizations are more successful when the government fully relinquishes control, when the bank is privatized to a strategic investor, and when foreign-owned banks are allowed to participate in the bidding. The privatization of Uganda Commercial Bank (UCB) to the South African bank Stanbic met all these criteria, suggesting that it is a likely candidate for success. But other features suggest reasons for caution: UCB dominated the Ugandan banking sector prior to privatization and the institutional environment in Uganda was less favorable than in many of the middle-income countries looked at in earlier empirical studies. Despite these concerns, the privatization appears to have been relatively successful. The portfolio of the privatized bank, which was cleaned prior to sale, remains relatively strong and profitability and credit growth are now on par with other Ugandan banks. Though market segmentation remains a concern since Stanbic faces little or no direct competition in many remote areas, some early results suggest that access to credit has improved for some hard-to-serve groups